Study on Biosynthesis, Structure and Roles of Coumarins in Nature: Characteristics, functions, and applications of coumarins (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Coumarin is a colorless crystalline solid with a sweet odor resembling the scent of vanilla and a bitter taste. It is found in many plants, where it may serve as a chemical defense against predators. Coumarin is a colorless crystalline solid with a sweet odor resembling the scent of vanilla and a bitter taste. It is found in many plants, where it may serve as a chemical defense against predators. By inhibiting synthesis of vitamin K, a related compound is applied as the prescription drug warfarin – an anticoagulant – to inhibit formation of blood clots, deep vein thrombosis, and pulmonary embolism.